EFEKTIVITAS MODEL PEMBELAJARAN READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) DALAM MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SEKOLAH DASAR NEGERI 1 CIMANGGU - Agung Kurniawan; Atot Sugiri; Mawa Nuralifa; Reisya Febriana; Asep Hermawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low reading comprehension skills of elementary school students, as indicated by their limited ability to understand the content of texts, identify important information, and answer questions based on the reading materials. The study aimed to determine the effectiveness of the Read, Answer, Discuss, Explain, and Create (RADEC) learning model in improving the reading comprehension skills of fourth-grade students at State Elementary School 1 Cimanggu. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 40 students, divided into two groups: 20 students in the experimental group and 20 students in the control group. Data were collected through reading comprehension tests administered during the pretest and posttest stages. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, the Wilcoxon Signed-Rank Test, the Mann–Whitney U Test, and the N-Gain Score analysis. The results showed that the mean pretest score of both groups was 62.75. After the implementation of the RADEC learning model, the mean posttest score of the experimental group increased to 90.50, while the control group achieved only 63.00. The Wilcoxon Signed-Rank Test indicated a significant improvement in the experimental group (Sig. = 0.000), whereas the control group showed no significant improvement (Sig. = 0.317). The Mann–Whitney U Test yielded an Asymp. Sig. (2-tailed) value of 0.000 (< 0.05), indicating a significant difference between the experimental and control groups. Furthermore, the N-Gain score of the experimental group was 0.745 (high category), while the control group obtained a score of 0.007 (low category), indicating that the RADEC learning model is effective in improving the reading comprehension skills of fourth-grade students at State Elementary School 1 Cimanggu.